The pharmacotherapeutics of sarcoidosis. Issue 1 (2nd January 2022) - Mangialardi, Patrick; Harper, Richart; Albertson, Timothy E
ABSTRACT: Introduction: Sarcoidosis is a multi-system, inflammatory, and granulomatous disease that can damage multiple organs. Several drugs have been used to treat sarcoidosis, but few have randomized-controlled trials (RCTs) to understand their efficacy. This lack of RCTs and the heterogenous nature of sarcoidosis makes for a challenge to the provider caring for these patients. Areas covered: Glucocorticoids remain the backbone of treatment of sarcoidosis. The side effect profile of glucocorticoids has resulted in the search for other sarcoid disease modifying drugs. This paper reviews the pharmacology, history, efficacy data, and adverse effects of alternative treatments. Most alternative sarcoidosis immune modulating treatments lack RCTs to evaluate their relative efficacy. Expert opinion: Because of the variability of disease presentation and progression, the treatment of sarcoidosis is best managed by expert clinicians with a firm understanding of the pharmacology, pharmacokinetics, monitoring requirements, counter-indications, and adverse effects of agents used. More RCTs that compare agents in well-defined sarcoid subgroups are clearly needed.